Developing a web-based LGBT cultural competency training for oncologists: The COLORS training. Issue 5 (May 2019) - Seay, Julia; Hicks, Amanda; Markham, Merry Jennifer; Schlumbrecht, Matthew; Bowman, Meghan; Woodard, Jennifer; Kollefrath, Austin; Diego, Daniela; Quinn, Gwendolyn P.; Schabath, Matthew B.
Highlights: LGBT cultural competency training for oncologists should be primarily interactive. Training should model effective communication between provider and patient. Training should focus on encouraging actionable and feasible behavior changes. Multi-disciplinary and community collaboration is crucial for training development. Abstract: Objective: Despite substantial LGBT cancer health disparities, there are no LGBT cultural competency trainings tailored for oncologists. Here we describe the systematic development of a web-based, oncology-focused LGBT cultural competency training. Methods: A literature review regarding LGBT cancer outcomes and competency training was conducted to identify potential training content. An expert panel meeting, including LGBT cancer survivors, cultural competency experts, oncologists, a web designer, and an instructional designer, was held to solidify the training content focus. Following the panel, the training was developed in collaboration with an instructional designer, a web designer, and LGBT community members. Results: The training modules include: 1) LGBT Basics; 2) Inclusive Environments; 3) Initiating Oncology Care with LGBT Patients; and 4) Issues in Cancer Survivorship among LGBT Patients. Module content is interactive, and models effective communication. Conclusion: The process of collaboration with a diverse group of stakeholders and three cancer centers in Florida has resulted in a practical and efficient web-based resource for LGBT cultural competency training for oncologists. Practice implications: Feedback from stakeholders indicates that training in this area is needed and will be well-received by oncologists. We are currently conducting an evaluation of this training among oncologists and LGBT community members.